An Eye-Tracking Assistive Device Improves the Quality of Life for ALS Patients and Reduces the Caregivers' Burden - Hwang, Chi-Shin; Weng, Ho-Hsiu; Wang, Li-Fen; Tsai, Chon-Haw; Chang, Hao-Teng (Journal of motor behavior, 2014)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease. In some cases, patients with ALS retain a normal level of consciousness but disease progression eventually results in generalized paralysis, which first impedes and then prevents oral communication. This communication obstacle can generate a great deal of stress for the patient, family, and caregiver. Here the authors ask whether the use of an eye-tracking assistive device can improve quality of life for ALS patients and relieves burden of their primary caregivers. Subjects were divided into two groups depending on whether they used (n = 10) or did not use (n = 10) an eye-tracking assistive device. The authors assessed patients' quality of life and severity of depression using the ALS Specific Quality of Life Instrument-Revised and the Taiwanese Depression Questionnaire, respectively. The Caregiver Burden Scale was used to assess the burden on caregivers. Our study shows that the eye-tracking assistive device significantly improved patients' quality of life, as compared with patients in the nonuser group (p <.01). The assistive device also reduced the burden on caregivers (p <.05). This is likely a result of the improvement of patient's autonomy and more effective communication between patient and caregiver.